THE ROLE OF THE MACROORGANISM IN THE MANIFESTATION OF PATHOGENIC PROPERTIES IN CONDITIONAL-PATHOGENIC MICROFLORA OF THE ORGANISM - Umarova T. A.; Kudratova Z. E.; Allamurodova X. (Web of Journals Publishing, 2024)
Some normal microorganisms of the macroorganism can, under certain conditions, cause subclinical and clinical manifestations of infectious diseases. Therefore, there is a growing need for a more detailed study of these microorganisms, the conditions that lead to the emergence of infectious diseases involving them, and the improvement of diagnostic, treatment, and prevention methods.
Keywords: infectious disease, normal microflora, pathogenic microorganisms, digestive tract, urinary system.